2018
DOI: 10.3389/fimmu.2018.00211
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Defensin 2 and 3 Promote Bacterial Clearance of Pseudomonas aeruginosa by Inhibiting Macrophage Autophagy through Downregulation of Early Growth Response Gene-1 and c-FOS

Abstract: Beta-defensins 2 and 3 (BD2 and BD3) are inducible peptides present at the sites of infection, and they are well characterized for their antimicrobial activities and immune-regulatory functions. However, no study has thoroughly investigated their immunomodulatory effects on macrophage-mediated immune responses against Pseudomonas aeruginosa (PA). Here, we use THP-1 and RAW264.7 cell lines and demonstrate that BD2 and BD3 suppressed macrophage autophagy but enhanced the engulfment of PA and Zymosan bioparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…In addition, in the infected cornea of mice, silencing of the murine orthologues of HBD2 and 3 resulted in increased production of proinflammatory cytokines, with a simultaneous increase in bacterial load (91). The effect on bacterial load is postulated to be due to the defensins [at low concentration of 1 µg/ml (0.2 µM)] inhibiting macrophage autophagy and in this way increasing phagocytic receptor expression leading to intracellular killing of the Pseudomonas aeruginosa (92). All these studies indicate that, under specific infections scenarios, defensins are capable of contributing to antiinflammatory response, or at least a rebalancing of the nature of the cellular response.…”
Section: Innate Suppressionmentioning
confidence: 99%
“…In addition, in the infected cornea of mice, silencing of the murine orthologues of HBD2 and 3 resulted in increased production of proinflammatory cytokines, with a simultaneous increase in bacterial load (91). The effect on bacterial load is postulated to be due to the defensins [at low concentration of 1 µg/ml (0.2 µM)] inhibiting macrophage autophagy and in this way increasing phagocytic receptor expression leading to intracellular killing of the Pseudomonas aeruginosa (92). All these studies indicate that, under specific infections scenarios, defensins are capable of contributing to antiinflammatory response, or at least a rebalancing of the nature of the cellular response.…”
Section: Innate Suppressionmentioning
confidence: 99%
“…Western blot was performed as described previously (28). Cells were rinsed three times with ice-cold PBS (pH 7.4) and treated with lysis buffer containing 1% (v/v) protease inhibitor mixture, 1 mM phenylmethylsulphonyl fluoride, and 1 mM DTT.…”
Section: Western Blotmentioning
confidence: 99%
“…Considering that c-fos and ERK pathway also have been found to join in the regulation of cell autophagy (Wu et al. 2018; Fung and Liu 2019), the findings of our research suggested that up-regulation of MEG3 attended to the influence of morphine on HT22 cell autophagy might be achieved by elevating c-fos expression and promoting ERK pathway activation.…”
Section: Discussionmentioning
confidence: 52%